ON THE PROBLEM OF OIL AND GAS REPLENISHMENT - I. G. Sazonov; D. A. Astapova (Наука. Инновации. Технологии, 2022)
Introduction: The article discusses the issues of the ongoing formation of hydrocarbons in oil and gas deposits and highlights the periodicity of such processes associated with the frequency of hydrocarbons and their migration channels generation. The main features of oil and gas deposits, which reserves are replenishing at the present time, are given Materials and research methods: The results of studies of deposits of the North Caucasus, as well as the generalization and analysis of publications about fields of the Volga-Ural, Caspian and other oil and gas regions were used. During the analysis, priority was given to thermodynamic, hydrogeological and geological-geochemical differences between oil and gas deposits Research results and discussion: The connection of oil and gas deposits with deeper zones of the litho-sphere is proved. The main features of ields with active modern replenishment of hydrocarbon reserves are given. The frequency of the hydrocarbon reserves replenishment, which depends, first of all, on the regime of tectonic processes is emphasized Conclusions The necessity of organizing monitoring of the processes of hydrocarbon's production and inflowing at several fields with clear signs of reserves replenishment has been substantiated